2018
DOI: 10.1155/2018/2024602
|View full text |Cite
|
Sign up to set email alerts
|

In VitroCytotoxicity andIn VivoAntimammary Tumor Effects of the Hydroethanolic Extract ofAcacia seyal(Mimosaceae) Stem Bark

Abstract: The present study was designed to evaluate the in vitro and in vivo antitumor effects of A. seyal hydroethanolic extract on breast cancer. The cytotoxicity of A. seyal extract was evaluated using resazurin reduction assay in 9 cell lines. Further, the protective effect of the hydroethanolic extract of A. seyal stem barks was evaluated on 7,12-dimethylbenz(a)anthracene- (DMBA-) induced breast cancer rat model. Incidence, burden, volume, and histological analysis of mammary tumors were measured. The Acacia seyal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
4
17
0
Order By: Relevance
“…The result from the study showed lower values of platelet count, indicating the usefulness of this extract in reducing blood platelet, and hence angiogenesis. This result is also in line with those of [18], that ethanolic extract of Acacia seyal on DMBA induced mammary tumours were able to reduce platelet concentration when compared to the DMBA-untreated group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The result from the study showed lower values of platelet count, indicating the usefulness of this extract in reducing blood platelet, and hence angiogenesis. This result is also in line with those of [18], that ethanolic extract of Acacia seyal on DMBA induced mammary tumours were able to reduce platelet concentration when compared to the DMBA-untreated group.…”
Section: Discussionsupporting
confidence: 91%
“…The various plants have shown to have anti-anaemic properties; this might be due to the high concentration of iron present in these plants and thus reduce risk of death of patients with cancer from heart failure. This commensurate with the works of Zingue, et al [18], which demonstrated that ethanolic extract of Acacia seyal on DMBA-induced mammary tumours were able to increase MCV, MCHC, MCH, RBC, PCV and haemoglobin concentration when contrasted to the DMBA un-treated animals. Table 3 demonstrates the white blood cell of DMBA administered albino rats, given the different plants extract.…”
Section: Discussionsupporting
confidence: 91%
“…Evaluation of the cytotoxic effect of EEP was carried out in 8 cells using Alamar Blue bioassay as reported by Zingue et al 22 Fluorescent excitation/emission wavelengths of 530/590 nm were recorded with an LS55 spectrofluorometer (Perkin Elmer; Becton Dickinson [San Jose, CA]). The CC 50 was calculated by nonlinear regression analysis using Graphpad prism 8.0 software.…”
Section: Methodsmentioning
confidence: 99%
“…Mammary glands, uterus, vagina, kidneys, and liver were dehydrated by a series of ethanol solution, embedded in paraffin blocks before cutting into 5 μ m sections, and stained with hematoxylin and eosin as previously reported by Zingue et al [9, 15]. Histomorphological changes were determined under an Axioskop 40 microscope connected to a computer where the image was transferred using MRGrab1.0 and Axio Vision 3.1 software (Zeiss Hallbergmoos, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding biochemical analysis, aspartate transaminase (AST) and alanine transaminase (ALT) activities were measured as previously reported [9, 15] using reagent kits from Fortress Diagnostics Limited (Muckamore, United Kingdom). Capillary glucose measurements were done on days 1 and 84 of the experiment.…”
Section: Methodsmentioning
confidence: 99%